Assessing the first wave of epidemiological studies of nanomaterial workers - Liou, Saou-Hsing; Tsai, Candace S J; Pelclova, Daniela; Schubauer-Berigan, Mary K; Schulte, Paul A (Journal of nanoparticle research, 2015)
The results of early animal studies of engineered nanomaterials (ENMs) and air pollution epidemiology suggest that it is important to assess the health of ENM workers. Initial epidemiological studies of workers' exposure to ENMs (<100 nm) are reviewed and characterized for their study designs, findings, and limitations. Of the 15 studies, 11 were cross-sectional, 4 were longitudinal (1 was both cross-sectional and longitudinal in design), and 1 was a descriptive pilot study. Generally, the studies used biologic markers as the dependent variables. All 11 cross-sectional studies showed a positive relationship between various biomarkers and ENM exposures. Three of the four longitudinal studies showed a negative relationship; the fourth showed positive findings after a 1-year follow-up. Each study considered exposure to ENMs as the independent variable. Exposure was assessed by mass concentration in 10 studies and by particle count in six studies. Six of them assessed both mass and particle concentrations. Some of the studies had limited exposure data because of inadequate exposure assessment. Generally, exposure levels were not very high in comparison to those in human inhalation chamber studies, but there were some exceptions. Most studies involved a small sample size, from 2 to 258 exposed workers. These studies represent the first wave of epidemiological studies of ENM workers. They are limited by small numbers of participants, inconsistent (and in some cases inadequate) exposure assessments, generally low exposures, and short intervals between exposure and effect. Still, these studies are a foundation for future work; they provide insight into where ENM workers are experiencing potentially adverse effects that might be related to ENM exposures.
Keywords: Sample size; Biological markers; Epidemiological studies; Longitudinal panel study; Nanoparticle exposure; Nanomaterial workers; Cross-sectional study